The 5th Canadian Symposium on Hepatitis C Virus: We Are Not Done Yet—Remaining Challenges in Hepatitis C. (24th October 2016) - van Buuren, Nicholas; Fradette, Lorraine; Grebely, Jason; King, Alexandra; Krajden, Mel; MacParland, Sonya A.; Marshall, Alison; Saeed, Sahar; Wilson, Joyce; Klein, Marina B.; Sagan, Selena M.
Abstract : Hepatitis C virus (HCV) affects approximately 268, 000 Canadians and results in more years of life lost than any other infectious disease in the country. Both the Canadian Institutes of Health Research (CIHR) and the Public Health Agency of Canada (PHAC) have identified HCV-related liver disease as a priority and supported the establishment of a National Hepatitis C Research Network. In 2015, the introduction of new interferon- (IFN-) free therapies with high cure rates (>90%) and few side effects revolutionized HCV therapy. However, a considerable proportion of the population remains undiagnosed and treatment uptake remains low in Canada due to financial, geographical, cultural, and social barriers. Comprehensive prevention strategies, including enhanced harm reduction, broader screening, widespread treatment, and vaccine development, are far from being realized. The theme of the 2016 symposium, "We're not done yet: remaining challenges in Hepatitis C, " was focused on identifying strategies to enhance prevention, diagnosis, and treatment of HCV to reduce disease burden and ultimately eliminate HCV in Canada.